APLIKASI MURAL BERTEMA KOLABORASI BUDAYA UNTUK MENINGKATKAN APRESIASI TERHADAP KESENIAN JAKARTA - Mariana; Danarto, Agus; Chandra, Edy; Lianto, Fermanto (Jurnal Serina Abdimas, 2023)
Jakarta consists of various unique cultures from various people from various regions. However, as with other regions that have local culture, Betawi is the culture of Jakarta's original ethnicity. However, in reality, Betawi culture and arts are increasingly being displaced by city culture and international culture which are more loved by its diverse population, especially Millennials. To introduce Betawi culture and arts which are rich and have their own charm, practical efforts are taken, one of which is through optimizing city visuals with mural media. Betawi, especially for the people around the Tomang sub-district and the general public who are active around the mural location. Betawi cultural elements such as ondel-ondel, tari topeng, tanjidor, pencak silat, kerak telor, and other Betawi cultural decorative ornaments will be collaborated harmoniously in the mural sketches that will be applied. The result of this mural PKM activity is a research paper regarding the role of a cultural-themed mural application in increasing public appreciation of Jakarta Arts and Intellectual Property Rights in the design concept implemented on the ex-mayor wall panels of West Jakarta.